Comprehensive Evaluation of ''Renong No.1'' Phyllanthus Emblica L. Quality Based on Principal Component Analysis - He SONG; Wei HE; Zuozuo LIU; Ruiting LI; Jie WU; Tian LIAO; Yan JIANG (Shipin gongye ke-ji, 2023)
The purpose of this study is to comprehensively evaluate the fruit quality of the new variety "Renong No.1" Phyllanthus emblica L. and determine its optimal harvesting period. 10 indexes such as edible rate and reducing sugar of 21 samples of "Renong No.1" picked in Binchuan county of Yunnan province from 2019 to 2021 were comprehensively evaluated by character analysis, variation analysis, correlation analysis and principal component analysis. The results showed that there were different in fruit quality of "Renong No.1" in different picking periods. The variation coefficients of edible rate, hardness, weight and diameter was 4.22%~17.08%. The variation coefficients of flavonoids, polyphenols, sucrose, reducing sugar, VC and total acid content were 9.45%~26.72%. The fruit firmness, edible rate, reducing sugar and polyphenol content all reached their peaks in the middle and early November in three years. Spearman correlation analysis showed that fruit weight, firmness and edible percentage were positively correlated with reducing sugar content (P<0.01), and negatively correlated with sucrose content (P<0.01), flavonoids content were positively correlated with VC, polyphenols and total acid content (P<0.05). This study extracted three principal components based on principal component analysis: PC1 represented fruit flavor index, PC2 represented nutrition index and PC3 represented appearance index. The cumulative contribution rate of three principal components was 81.58%. The comprehensive ranking results showed that the fruit quality in late October and early November was better. In this study, a mathematical model based on principal component analysis was established to comprehensively evaluate the fruit quality of the new variety "Renong No.1" Phyllanthus emblica L., and the optimal harvest time was from the end of October to the middle of November with sweet flavor, full appearance and high content of VC, total phenols and total flavonoids.